ChemInform Abstract: High‐Pressure Synthesis and Crystal Structure of the Mixed Valent Iron Borate Fe8B15O28(OH)8. Issue 5 (4th February 2014) - Neumair, Stephanie C.; Perfler, Lukas; Winter, Florian; Poettgen, Rainer; Heymann, Gunter; Huppertz, Hubert
Abstract The new FeII/FeIII mixed‐valent title compound is obtained from a stoichiometric mixture of Fe2O3 and H3BO3 under high pressure/high temperature conditions (BN crucible, multianvil device, 12 GPa, 850 °C, 15 min).